2013
DOI: 10.1021/ar3002624
|View full text |Cite
|
Sign up to set email alerts
|

Gas Transport across Hyperthin Membranes

Abstract: The use of organic polymeric membranes to separate gaseous mixtures provides an attractive alternative to other methods such as selective adsorption and cryogenic distillation. The primary advantages of membrane-based separations are their relative energy efficiency and lower costs. Because the flux of a gas across a membrane is inversely proportional to the membrane's thickness, this method relies on fabricating membranes that are as thin as possible. However, as researchers have tried to produce "hyperthin" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…This is of particular importance for largescale gas separations such as carbonc apture membranes, where as urface area of the membrane of many square kilometers is required. [3] In this study,w eh ave shown that PIM-EA-TB(H 2 )f orms homogeneous and stable monolayersa tt he air-wateri nterface (see the Supporting Information and Figure S1) that can be transferred onto differents ubstrates by using the LS method.Each PIM-EA-TB(H 2 )L Sm onolayer deposited had at hickness of approximately 1nma nd severalm onolayers could be successivelyd eposited by using this procedure to obtain an ultrathin selective layer with the desired thickness. Highly rigid PIMs composed of bridged bicyclic units, such as ethanoanthracene (EA) and Trçger's Base (TB), [7] are of particular interest due to their highers electivity.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…This is of particular importance for largescale gas separations such as carbonc apture membranes, where as urface area of the membrane of many square kilometers is required. [3] In this study,w eh ave shown that PIM-EA-TB(H 2 )f orms homogeneous and stable monolayersa tt he air-wateri nterface (see the Supporting Information and Figure S1) that can be transferred onto differents ubstrates by using the LS method.Each PIM-EA-TB(H 2 )L Sm onolayer deposited had at hickness of approximately 1nma nd severalm onolayers could be successivelyd eposited by using this procedure to obtain an ultrathin selective layer with the desired thickness. Highly rigid PIMs composed of bridged bicyclic units, such as ethanoanthracene (EA) and Trçger's Base (TB), [7] are of particular interest due to their highers electivity.…”
mentioning
confidence: 78%
“…In this contribution, composite membranes have been obtained by the successive deposition of approximately 1nmt hickm onolayers of ap olymer of intrinsic microporosity (PIM) on top of dense membranes of the ultra-permeable poly[1-(trimethylsilyl)-1-propyne] (PTMSP). [3] For composite multilayer membranes, the cost of the polymer selectivel ayer would be significantly reduced by using ultrathin films, therefore allowing the use of high-cost, high-performance materials. [1] An ideal membrane should be as thin as possible, to maximize the flux (i.e.,permeance) across the membrane, as selectiveaspossible, to achieve an efficient separation, and mechanically robust.…”
mentioning
confidence: 99%
“…As a result, the CO 2 permeance was below the detection limit and the estimated minimum H 2 /CO 2 selectivity was 190. It should be noted that these as-developed polyelectrolyte multilayer membranes showed the exceptional H 2 /CO 2 selectivity combined with the extremely low gas permeance, even though the membrane thickness was only a dozen or even a few nanometers [166]. Therefore, these membranes show great potential in gas barrier applications, however, they are generally unattractive in large-scale hydrogen purification.…”
Section: Polyelectrolyte Multilayers Membranesmentioning
confidence: 99%
“…However, it is difficult to fabricate a defect-free ultrathin film on a large scale for gas separations. [18][19][20] There have been advances on development of novel membrane materials, membrane structures and membrane formation processes to increase the separation performance of membranes, but much more work is still needed to apply them in practice.…”
Section: Introductionmentioning
confidence: 99%